Strategic redirection in large management buyouts: The evidence from post‐buyout restructuring activity - Seth, Anju; Easterwood, John C. (Strategic Management Journal, 1993)
Abstract This study examines the nature of post‐transaction restructuring activities for 32 large U.S. corporations that underwent management buyouts between 1983–89. This study (i) provides evidence on the extent and type of divestment and acquisition activities under private ownership; (ii) documents the outcomes associated with MBOs and the longevity of the buyout organization; and (iii) investigates the claim that buyouts are primarily mechanisms for breaking up public corporations and selling the pieces to related acquirers. The balance of the evidence indicates that restoring strategic focus is an essential function of the buyout for these large firms. However, the evidence also indicates that the buyout organization does continue to operate significant parts of the prebuyout firm. By far the majority of firms continue to meet their debt obligations satisfactorily during the buyout phase. Finally, the evidence indicates that asset sales to related acquirers derive more from efficiency considerations than market power.